Hindcasting Ecosystem Functioning Change in an Anthropogenized Estuary: Implications for an Era of Global Change - Fang, Xiaoyu; Cozzoli, Francesco; Smolders, Sven; Knights, Antony; Moens, Tom; Soetaert, Karline; Van Colen, Carl (Frontiers in Marine Science, 2021)
Understanding how altered hydrodynamics related to climate change and anthropogenic modifications affect ecosystem integrity of shallow coastal soft-sediment environments requires a sound integration of how species populations influence ecosystem functioning across heterogeneous spatial scales. Here, we hindcasted how intertidal habitat loss and altered hydrodynamic regimes between 1955 and 2010 associated with geomorphological change to accommodate expansion in anthropogenic activities in the Western Scheldt altered spatial patterns and basin-wide estimates of ecosystem functioning. To this end we combined an empirically derived metabolic model for the effect of the common ragworm Hediste diversicolor on sediment biogeochemistry (measured as sediment oxygen uptake) with a hydrodynamic and population biomass distribution model. Our integrative modeling approach predicted an overall decrease by 304 tons in ragworm biomass between 1955 and 2010, accounting for a reduction by 28% in stimulated sediment oxygen uptake at the landscape scale. Local gains or losses in habitat suitability and ecosystem functioning were primarily driven by changes in maximal current velocities and inundation regimes resulting from deepening, dredging and disposal practices. By looking into the past, we have demonstrated how hydro- and morphodynamic changes affect soft-sediment ecology and highlight the applicability of the integrative framework to upscale anticipated population effects on ecosystem functioning.